Answer: x = 2 , y = 3.5
Explanation:
Given :
2y = -x + 9 ......................... equation 1
3x -6y = - 15 ........................ equation 2
Solving the system of linear equations by substitution method , we will make x the subject of the formula from equation 1 , that is
2y = -x + 9
x = 9 - 2y ........................... equation 3
Substitute x = 9 - 2y into equation 2 , equation 2 then becomes :
3 ( 9 - 2y ) - 6y = - 15
27 - 6y - 6y = - 15
27 - 12y = - 15
27 + 15 = 12y
42 = 12y
y = 3.5
substitute y = 3.5 into equation 3 to get the value of x ,
x = 9 - 2y
x = 9 - 2 (3.5 )
x = 9 - 7
x = 2
Therefore :
x = 2 , y = 3.5